Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits - Mifsud, Borbala; Witkowska, Katarzyna; Tzanis, Evan; Velez Edwards, Digna R.; Wilson, Peter W. F.; Esko, Tonu; Almgren, Peter; Debette, Stéphanie; Li-Gao, Ruifang; Qian, Yong; Sargurupremraj, Muralidharan; Thériault, Sébastien; et al. (Nature genetics, 2018)
High blood pressure is a highly heritable and modifiable risk factor for cardiovascular disease. We report the largest genetic association study of blood pressure traits (systolic, diastolic and pulse pressure) to date in over 1 million people of European ancestry. We identify 535 novel blood pressure loci that not only offer new biological insights into blood pressure regulation but also highlight shared genetic architecture between blood pressure and lifestyle exposures. Our findings identify new biological pathways for blood pressure regulation with potential for improved cardiovascular disease prevention in the future. Association analyses in over 1 million individuals identify 535 new loci influencing blood pressure traits. The results provide new insights into blood pressure regulation and highlight shared genetic architecture between blood pressure and lifestyle exposures.